Efektivitas Program Corporate Social Responsibility Karawang Berseri (Bebas Kekerasan Perempuan dan Anak Semakin Maju dan Mandiri) di Kelurahan Karawang Kulon Kecamatan Karawang Barat Kabupaten Karawang - Tri Wahyu Utami; Haura Atthahara; Gun Gun Gumilar (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to study and find out about the Effectiveness of the Karawang Berseri Corporate Social Responsibility Program (Free of Violence against Women and Children More Advanced and Independent) in Karawang Kulon Village, West Karawang District, Karawang Regency. The theory used is Edy Sutrisno's Effectiveness in Lailatul Wahdah Agustina (2022) with 4 indicators in the form of Program Understanding, Targeting, Achievement of Goals and Real Change. This study used a qualitative descriptive method with data collection techniques carried out through interviews, observations and documentation studies. The results of the discussion of this study indicate that the CSR program of Karawang Berseri in the Village of Karawang Kulon runs optimally in all dimensions, but still needs improvement because cases of sexual violence continue to increase every year.